2018
DOI: 10.1371/journal.pntd.0005988
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating the sustainability, scalability, and replicability of an STH transmission interruption intervention: The DeWorm3 implementation science protocol

Abstract: Hybrid trials that include both clinical and implementation science outcomes are increasingly relevant for public health researchers that aim to rapidly translate study findings into evidence-based practice. The DeWorm3 Project is a series of hybrid trials testing the feasibility of interrupting the transmission of soil transmitted helminths (STH), while conducting implementation science research that contextualizes clinical research findings and provides guidance on opportunities to optimize delivery of STH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…These include a safe water supply, appropriately constructed and maintained sanitation infrastructure that ensures safe disposal of human excreta, the promotion of hygiene such as handwashing plus bathing, and the management of water in the home. Studies have shown that the provision of additional interventions should allow the suppression of the prevalence of STH and schistosomiasis infection to very low levels, achieved through MDA, to be sustained once transmission has deemed to be broken in defined settings such that MDA can cease in these settings [4951]. The Geshiyaro Project is the first large-scale project, addressing a zone of 1.9 million inhabitants, to provide WaSH facilities combined with MDA within different study arms which permits, in principle, the assessment of the relative benefits of MDA targeted at the whole community, whole community MDA plus WaSH, and MDA targeted at SAC.…”
Section: Discussionmentioning
confidence: 99%
“…These include a safe water supply, appropriately constructed and maintained sanitation infrastructure that ensures safe disposal of human excreta, the promotion of hygiene such as handwashing plus bathing, and the management of water in the home. Studies have shown that the provision of additional interventions should allow the suppression of the prevalence of STH and schistosomiasis infection to very low levels, achieved through MDA, to be sustained once transmission has deemed to be broken in defined settings such that MDA can cease in these settings [4951]. The Geshiyaro Project is the first large-scale project, addressing a zone of 1.9 million inhabitants, to provide WaSH facilities combined with MDA within different study arms which permits, in principle, the assessment of the relative benefits of MDA targeted at the whole community, whole community MDA plus WaSH, and MDA targeted at SAC.…”
Section: Discussionmentioning
confidence: 99%
“…lumbricoides and the other STH infections. Such awareness has resulted in the expansion of infection and risk mapping efforts [49] and operational research studies intended to improve, expand, and more fully understand the impacts associated with interventions [1015]. Similarly, due to exponential improvements in approaches to mathematical modelling, the roles played by these valuable tools for shaping and informing the STH programmatic decision making process continue to increase [56, 1618].…”
Section: Introductionmentioning
confidence: 99%
“…Two articles consisted of research protocols that had not yet reported on findings, and therefore, some of the items in the RATS tool could not be applied to assess the quality of these articles. 15,16 Additionally, 1 article 17 is a conference proceeding and 1 article 18 is an executive summary instead of a journal publication and therefore yielded a lower quality score based on the RATS assessment tool. Studies were assessed for quality independently by 2 researchers (TS and GDB), and any disagreements were resolved through discussion during an in-person meeting.…”
Section: Quality Assessment Toolmentioning
confidence: 99%
“…Of those 8 studies, 6 were reports of research study results [17][18][19][20][21][22] and 2 were protocols for studies. 15,16 Two publications were from the same study, 19,20 leaving 7 distinct studies included.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation